An Increase of Excitatory-to-Inhibitory Synaptic Balance in the Contralateral Cortico-Striatal Pathway Underlies Improved Stroke Recovery in BDNF Val66Met SNP Mice. (December 2019) - Qin, Luye; Actor-Engel, Hannah S.; Woo, Moon-Sook; Shakil, Faariah; Chen, Yi-Wen; Cho, Sunghee; Aoki, Chiye
Despite negative association in cognition and memory, mice harboring Val66Met BDNF SNP (BDNF M/M ) exhibit enhanced motor recovery accompanied by elevated excitatory synaptic markers VGLUT1 and VGLUT2 in striatum contralateral to unilateral ischemic stroke. The cortico-striatal pathway is a critical gateway for plasticity of motor/gait function. We hypothesized that enhanced excitability of the cortico-striatal pathway, especially of the contralateral hemisphere, underlies improved motor recovery. To test this hypothesis, we examined the key molecules involving excitatory synaptogenesis: Thrombospondins (TSP1/2) and their neuronal receptor α2δ-1. In WT brains, stroke induced expressions of TSP1/2-mRNA. The contralateral hemisphere of BDNF M/M mice showed heightened TSP2 and α2δ-1 mRNA and protein specifically at 6 months post-stroke. Immunoreactivities of TSPs and α2δ-1 were increased in cortical layers 1/2 of stroked BDNF M/M animals compared with BDNF M/M sham brains at this time. Areal densities of excitatory synapses in cortical layer 1 and striatum were also increased in stroked BDNF M/M brains, relative to stroked WT brains. Notably, the frequency of GABAergic synapses was greatly reduced along distal dendrites in cortical layer 1 in BDNF M/M brains, whether or not stroked, compared with WT brains. There was no effect of genotype or treatment on the density of GABAergic synapses onto striatal medium spiny neurons. The study identified molecular and synaptic substrates in the contralateral hemisphere of BDNF M/M mice, especially in cortical layers 1/2, which indicates selective region-related synaptic plasticity. The study suggests that an increase in excitatory-to-inhibitory synaptic balance along the contralateral cortico-striatal pathway underlies the enhanced functional recovery of BDNF M/M mice.